Meningkatkan Metode Pengajaran Kompetensi Belajar Mandiri dalam Lingkungan Digital - Nhung Kim Thi Vu; Thanh Chi Phan; Thanh Tu Ngo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
The world is changing of the 4th Industrial Revolution and the digital era, it is urgent to apply digital transformation in education. Innovating teaching and learning methods in the digital environment based on enhancing self-learning capacity of learners is essential to achieve digital transformation effectively in education and training. This study has proposed three solutions for self-study based teaching method in the digital environment in higher training, especiall in technical universities: (1) experimental self-study in the digital environment, (2) innovating teaching method of self-study in the digital environment, (3) innovating the self-study teching method to improve memory capacity in the digital environment. An objective of this study to clarify the term